Chromosome and pollen morphology of the rare endemic Centaurae lycopifolia Boiss. & Kotschy - Gomurgen, AN; Erkara, I Potoglu; Altnozlu, H (Bangladesh Journal of Botany, 2011)
Chromosome and pollen morphology of Centaurea lycopifolia Boiss. & Kotschy were studied. The chromosome number is 2n = 34 with haploid karyotype formula 9m + 9sm. Metaphase chromosome length ranging from 6.16 to 2.23 μm and the total haploid chromosome length was 65, 85 μm. The light and scanning electron microscope investigations revealed spheroidal-subprolate, the amb triangular and tricolporatae pollens in the taxon. Exine ornamentation was tectatae and microechinate-scabrate. Key words: Centaurea lycopifolia; Chromosome; Pollen morphology; Endemic; Turkey DOI: 10.3329/bjb.v39i2.7484 Bangladesh J. Bot. 39(2): 223-228, 2010 (December)